Dampak Boikot Terhadap Anjloknya Harga Saham PT. Unilever - Raihan Sultani Matondang; Annio Indah Lestari Nasution (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2024)
The decline in shares of this giant company tends to be associated with a boycott of products that support Israel over the humanitarian crisis of military attacks on Palestinian civilians. Boycott actions in Indonesia are becoming increasingly popular with the publication of MUI fatwa number 83 of 2023 concerning the law of support for Palestine, so researchers are interested in conducting further research regarding the impact of boycotts on share prices at PT. Unilever. This research uses mixed methods, namely qualitative and quantitative research types. Qualitative research in this study uses a literature study approach, the data sources in this study are secondary data obtained from books, journals and government policies related to the theme. Then it is analyzed and taken according to data requirements. Meanwhile, quantitative research was carried out by testing daily stock price data accessed via www.finance.Yahoo.com with SPSS 25. The methods used in this quantitative research were the Kolomogorov-Smirnov Test, the Paired Samplet-Test, and the Wilcoxon Signed Rank Test. The observation period consisted of 3 intervals, namely before the boycott action, after the boycott action and after the issuance of MUI fatwa no. 83 of 2023. The test results prove that there is no difference in stock prices before and after the announcement of the boycott movement. However, after the MUI issued fatwa no. 83 of 2023 which states support for Palestine, share prices weakened. So there is a significant difference between share prices before the boycott of PT products. Unilever and after the MUI fatwa.